Factors Affecting Negative Symptoms in Schizophrenia and Their Relationship with Anxiety and Depression - Zeng G; Liang R; Xiao L; Cao W; Zhou W; Wang W; Liu C; Zhou H; Shi X; Chen B; Chen W (Neuropsychiatric Disease and Treatment)
Gang Zeng,1,2,* Rongyu Liang,2,3,* Lingxian Xiao,2,4,* Weiye Cao,5 Wenqing Zhou,2,6 Wen Wang,5 Cuixia Liu,2,7 Huarong Zhou,1,2 Xiaolei Shi,1,2 Ben Chen,1,2 Wanhua Chen2,4 1Geriatric Neuroscience Center, The Affiliated Brain Hospital, Guangzhou Medical University, Guangzhou, People’s Republic of China; 2Key Laboratory of Neurogenetics and Channelopathies of Guangdong Province and the Ministry of Education of China, Guangzhou Medical University, Guangzhou, People’s Republic of China; 3Department of Geriatric Psychiatry, The Affiliated Brain Hospital, Guangzhou Medical University, Guangzhou, People’s Republic of China; 4Department of Nursing, The Affiliated Brain Hospital, Guangzhou Medical University, Guangzhou, People’s Republic of China; 5School of Nursing, Guangzhou Medical University, Guangzhou, People’s Republic of China; 6Adult Psychiatry Department, The Affiliated Brain Hospital, Guangzhou Medical University, Guangzhou, People’s Republic of China; 7Chronic Psychiatry Department, The Affiliated Brain Hospital, Guangzhou Medical University, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wenqing Zhou, Adult Psychiatry Department, Affiliated Brain Hospital of Guangzhou Medical University, 36 mingXin Road, Liwan District, Guangzhou, People’s Republic of China, Tel +86 15918636953, Email 996459134@qq.com Weiye Cao, School of Nursing, Guangzhou Medical University, 195 Dongfeng West Road, Yuexiu District, Guangzhou, People’s Republic of China, Tel +86 13149399874, Email 1271932456@qq.comObjective: Negative symptoms significantly impair daily functioning and worsen clinical outcomes. Meanwhile, these symptoms are closely linked to anxiety and depression, further complicating prognosis. The mechanisms underlying these relationships remain unclear. This study aims to identify the factors influencing negative symptoms in schizophrenia and examine their relationship with anxiety and depression to guide more effective interventions and improve patient outcomes.Methods: This study recruited 300 inpatients with schizophrenia from October 2022 to May 2023. Sociodemographic data and clinical characteristics were collected via a self-designed questionnaire. Negative symptoms, depression, and anxiety were assessed using the SANS, HAMD, and HAMA scales, respectively.Results: Multiple regression analysis indicated that familial support (β = − 1.285, P = 0.005), friend support (β = − 0.797, P = 0.032), sleep quality (β = 2.307, P < 0.001), anxiety (β = 0.264, P = 0.004), and depression (β = 0.324, P = 0.007) were the main factors influencing negative symptoms. After adjusting for the duration of psychiatric disorder and type of antipsychotic medication as covariates, the above factors remained primary contributors to negative symptoms.Conclusion: Enhancing familial support, friend support, and addressing emotional health and sleep disturbances are strategies that may alleviate negative symptoms in patients with schizophrenia.Keywords: negative symptoms, anxiety, depression, schizophrenia, mental health